PENGARUH SISTEM ONE PIECE FLOW DAN BUDAYA KAIZEN TERHADAP KINERJA KARYAWAN PT YAMAHA MUSIC MFG INDONESIA - Dwi Safitri, Dina; Haryanto, Joni (JAMBIS : Jurnal Administrasi Bisnis, 2024)
In the current digital era, employee performance preferences for ease and comfort whencarrying out the production process have increased significantly, PT Yamaha MusicManufacturing Indonesia (YMMI) uses the One Piece Flow System and Kaizen Culture to makethe production process easier for employees. This research aims to determine the influence ofthe One Piece Flow System and Kaizen Culture on the performance of PT YMMI employees.The research adopts a quantitative approach using survei methods. The sample includes 100respondents who are employees of PT YMMI. Data analysis utilizes multiple linear regression.The research result show that the One Piece Flow System (X1) partially has a positive andsignificant impact of 23,8% on Employee Performance (Y) at PT Yamaha Music ManufacturingIndonesia. Partially, Kaizen Culture (X2) has a 34,1% positive and significant impact onEmployee Performance (Y) at PT Yamaha Music Manufacturing Indonesia. Together the OnePiece Flow System (X1) and Kaizen Culture (X2) have a positive and significant effect on PTYamaha Music Manufacturing Indonesia’s Employee Performance (Y) by 36,7% and remaining63,3% is influenced by other variables that are not researched.